Burden of vaccine-preventable diseases, trends in vaccine coverage and current challenges in the implementation of the expanded program on immunization: A situation analysis of Cameroon - Che Henry Ngwa; Brigitte-Carole Keumatio Doungtsop; Rengerline Bihnwi; Ngo Valery Ngo; Niendum Mediatrice Yang (Taylor & Francis Group, 2022)
The discovery and development of vaccines remain one of the major successes of global health with millions of lives saved every year through routine vaccination. Although vaccines provide a safe and cost-effective solution to vaccine-preventable diseases (VPDs), VPDs are still a serious public health problem in most parts of the world, especially in sub-Saharan Africa (SSA) and Asia. In this review, we discuss the burden of VPDs and vaccine coverage several decades after the introduction of the Expanded Program on Immunization (EPI) in Cameroon. We also discuss how different factors affect the implementation of the EPI, highlighting context-specific factors such as the ongoing civil conflict in Cameroon, and the presence of other infectious diseases like COVID-19.